Form and Meaning: A Transformational Generative Approach to Syntax-Semantics Interface - Rebwar Qasim Ibrahim; Lanja Abdul Razzaq Dabbagh (QALAAI ZANIST JOURNAL, 2023)
The interrelation between syntactic and semantic properties of sentences has puzzled transformational generative syntacticians for decades. This paper approaches the issue from a transformational generative (TGG) point of view. It aims to show three approaches within TGG to syntax-semantics interface, and the problems each approach faces. The questions tackled here include: what is the general assumption concerning the relation between form and meaning that guides TGG in its dealing with the interface problem? How is this assumption realized in TGG’s compartmentalization of grammar? What are the problems with each model of grammar when it comes to syntax-semantics interface? This paper hypothesizes that TGG assumes the syntactic component of language to be the sole generative component; hence it considers the sematic component to be merely interpretive; the paper also hypothesizes that the interrelation between structure and meaning has been a key factor in several reorganizations of grammar proposed by TGG. This paper adopts a descriptive method, although on some issues, including the problem of the logical form (LF), it brings in solutions proposed by semanticists from outside TGG. The paper concludes that even LF has been prone to several objections, as it is not quite clear how syntactic properties are encoded in such a way as to be accessible to conceptual components of the mind.